Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pasien Pada Masa Pandemi COVID-19 Di Rumah Sakit Permata Pamulang: Relationship between Family Support and Patient Anxiety Levels during the COVID-19 Pandemic at Permata Pamulang Hospital - Tampani, Yance (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: COVID-19 is an infectious disease caused by a new Coronavirus. Common symptoms are fever, weakness, cough, cramps, and diarrhea. The very high spread of COVID-19 can cause mental health and psychosocial problems for the client, the client's family, the client's neighbors, and even medical personnel. The psychological impact due to the provisions of COVID-19 is more dangerous than the disease. The causes of anxiety or fear are caused by a lack of knowledge and information, anxiety, coping mechanisms, and support systems that exist in every society. This study aims to determine the relationship between family support and patient anxiety levels during the COVID-19 pandemic at Permata Pamulang Hospital.  Methods: The design of this study used a quantitative approach with a cross-sectional approach performed on cancer patients undergoing treatment at the hospital. The population in this study were all inpatients on the 3rd floor of Permata Pamulang Hospital. The sample in this study amounted to 50 respondents. The research instrument used a family support questionnaire and a standard Hamilton rating scale for anxiety (HRS-A) questionnaire. This study used Spearman rank analysis. Results: Based on the results of the study it was shown that almost half (34,0%) of patients who received moderate family support had moderate levels of anxiety, a small proportion (20,0%) of patients who received high family support had moderate anxiety and a small proportion (8,0%) patients who get low family support experience severe anxiety. The p-value is 0,000 or the probability is less than 0,05 (0,000 < 0,05). Discussion: There is a significant relationship between family support and the level of patient anxiety during the COVID-19 pandemic at Permata Pamulang Hospital with a moderate level of closeness and a negative sign indicating that the higher the family support, the lower the level of anxiety.